Legal and ethical accountability for nursing errors: disclosure and apology - Westrick, Susan J (Sigma Theta Tau International's 28th International Nursing Research Congress, 2017)
Citation Key Alias: lens.org/128-339-545-333-679
Keywords: dept.nur; ⛔ No DOI found

Essentials of nursing law and ethics - Westrick, Susan J. (Jones & Bartlett Learning, 2014)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Sabbatical leave report: sabbatical Fall 2012 / submitted by: Susan J. Westrick, Professor, Department of Nursing. - Westrick, Susan J. (2012)
This sabbatical project involved re-writing as the sole author a previously co-authored textbook, Essentials of Nursing Law and Ethics (2009), devoted to traditional and contemporary legal and ethical concerns for nursing students and practicing nurses.
Keywords: dept.nur; faculty_collection; sabbatical_report

Evidence-Based Nursing Guide to Legal & Professional Issues. - Westrick, Susan J.; Lippincott Williams & Wilkins (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
Keywords: Law and legislation; Nursing; United States; dept.nur; faculty_collection

Disclosure of errors and apology: law and ethics - Westrick, Susan J.; Jacob, Nyshi (JNP-Journal for Nurse Practitioners, 2016)
Error disclosure and apology are evolving concerns for advanced practice nurses who have increased exposure to liability. Error disclosure is required by regulatory agencies and the American Nurses Association Code of Ethics for Nurses, yet barriers to disclosure exist and nurse practitioners may not be aware of state apology laws that protect some statements from use in civil lawsuits for negligence or malpractice. Two law cases that apply apology laws are reviewed to illustrate these protections. Best practices for error disclosure are presented, and nurse educators are urged to include error disclosure content in nurse practitioner curricula as part of safety and quality education.
5 citations (Crossref) [2023-10-31] tex.eissn: 1878-058X tex.unique-id: ISI:000369613500021
Keywords: dept.nur

Fostering Nursing Students' Moral Decision-Making Through Use of an Affective Learning Module - Morrill, Deborah; Westrick, Susan J. (Nurse Educator, 2022)
Background: The emphasis on disciplinary and preventive approaches to combating academic misconduct does little to foster student professional identity and core nursing value formation. Problem: There is a need for pedagogy designed to navigate moral decision-making within ambiguous areas of practice as nursing students integrate personal and professional values while becoming a nurse. Approach: Rest's theory of moral development offers a framework for constructing purposeful affective learning activities that operationalize moral sensitivity, judgment, motivation, and character, whereas Krathwohl's theory provides a means to identify affective learning objectives. Offering prelicensure nursing students an opportunity to discuss, reflect on, and consider actions and consequences associated with academic and practice-based situations forms the basis for this affective learning module that fosters connections between academic and professional behaviors of integrity. Conclusion: Rest's theoretical model provides a viable structured approach to moral development. Curriculum designed to engage moral decision-making offers an innovative approach to cultivating student integrity.
1 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Essentials of Nursing Law and Ethics - Westrick, Susan J. (Jones and Bartlett Publishers, 2009)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (Jones and Bartlett, 2006)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (SLACK Inc., 2000)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching